Tribological behaviour of the double FeCoNiCrCux middle-entropy alloy coatings - Cai, Yang Chuan; Manladan, Sunusi Marwana; Luo, Zhen (Maney Publishing, 2019)
In the present research, the double FeCoCrNiCux medium-entropy alloy coatings were manufactured on Cr12MoV die steel by laser cladding technology. The cross-section, microstructure, phase, micro-hardness, and tribological behaviour of the coatings were investigated systemically. The dilution effect of the substrate had the weaker effect on the second layer compared to the first layer. The double FeCoCrNiCux cladding layers only had a single face-centred cubic phase led to the lower micro-hardness and wear resistance. The different atomic radius of the alloying elements in the coatings generated a large lattice dislocation. The face-centred cubic structure of coatings had a higher hardness than that of the traditional face-centred cubic structure. The Cu element is easy to segregate at the grain boundaries to form the Cu-rich solid solution.